ESG performance and organizational resilience: Based on an 'extreme heat event' - Haiyue Liu; Qin Zhang; Xin Xia; Xite Yang; Zhimin Yi; Longfei Yue; Linya Huang (Borsa İstanbul Review, 2024)
This study evaluated the organizational resilience of Chinese listed companies under extreme heat events based on the cumulative abnormal return of stocks during severe environmental disturbances. Based on institutional, stakeholder, and risk management theories, the extreme heat event in August 2022 was chosen as the research setting to evaluate the relationships between environmental, social, and governance (ESG) performances and organizational resilience. Results showed that ESG performances significantly improve company resilience in market short-term response. The significantly improved resilience effects were observed in non-state-owned enterprises and companies in low-carbon pilot cities. Further analysis revealed that companies with varying levels of ESG performances demonstrate significant differences in long-term profitability potential. This study has important implications for further research on the effect of ESG performance on company resilience and provides a basis for enhancing company stability and flexibility during frequent extreme weather events.
Keywords: 330; Extreme heat events; ESG; Resilience; Sustainability